How Clinicians Recall Experiences - Kochen, M. (Methods of Information in Medicine, 1983)
Primary care physicians rely on their experience to a greater extent than on the literature, interaction -with colleagues, meetings, or what they have learned in medical school when making judgments about diagnosis and treatment. They use conventional files ordered most commonly by patient’s last name to aid in recall of specific experiences, though a patient’s name is not always remembered when necessary. Analysis of these hypotheses suggests the introduction of microcomputer-based information systems in physicians’ offices in order to augment the memory of clinicians for specific experiences.
Keywords: Computers in Medical Office; Recall of Clinical Experience; Information Systems for Clinicians